KAJIAN TINGKAT KOMPLEKSITAS MASALAH PADA BUKU PEMBELAJARAN MATEMATIKA BERBASIS TAKSONOMI SOLO - Nur Asitah; Fatkul Anam; Agung Purnomo (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2022)
Mathematics is an important subject in schools, as well as among other complex subjects. Of the various difficulties of research, it is always difficult for mathematics to be the most important subject for every student. Students have difficulties that can make mistakes when working on math problems. One way to identify the appropriateness of students' responses to math problems is the SOLO taxonomy. SOLO taxonomy plays a role in determining the quality of student responses to the problems faced. Researchers used a Student Textbook entitled